(untitled) - Kleinknecht, Alfred (New York, 1987)
Theories about an alleged 45-60 year's pulsation in economic life (the Kondratieff-Schumpeter cycle) have experienced a Renaissance during the last decade. This book draws attention to some early,... ....
Keywords: Đổi mới kinh tế,Economics Innovation